Efficacy of low carbohydrate and ketogenic diets in treating mood and anxiety disorders: systematic review and implications for clinical practice - Daniel M. Dietch; Jess Kerr-Gaffney; Meghan Hockey; Wolfgang Marx; Anu Ruusunen; Allan H. Young; Michael Berk; Valeria Mondelli (BJPsych Open, 2023)
Background There is mounting interest in the potential efficacy of low carbohydrate and very low carbohydrate ketogenic diets in various neurological and psychiatric disorders.